Manhaj Al-Wasṭiyyah Yûsuf Al-Qaraḍâwi dalam Kitab Fatawa Muˋâṣirah - Safnita Novriati (Syarah: Jurnal Hukum Islam dan Ekonomi, 2022)
This study aims to find out how the understanding of al-wasaṭiyyah taught by Islam according to the Qur'an and Hadith, understand Yûsuf al-Qaraḍâwi's thoughts about manhaj al-wasaṭiyyah, and how the application of manhaj al-wasaṭiyyah in the Muˋâṣirah Fatawa book. This research uses a qualitative descriptive research approach with library research. In data collection techniques, the author examines the books related to Yûsuf al-Qaraḍâwi which consist of primary data, namely the works of al-Qaraḍâwi which are related to manhaj al-wasaṭiyyah especially Fiqh al-Wasaṭiyyah al-Islamiyah wa at-Tajdîd, Sentences fî al -Wasaṭiyyah al-Islamiyah wa Maˋâlimiha and the book Fatawa Muˋâṣirah. While secondary data are books or articles about Yûsuf al-Qaraḍâwi's thoughts which are the results of interpretations of other people and other books related to the object of this study. In terms of analyzing data, the author uses the method of content analysis. Al-wasaṭiyyah is one of the characteristics of Islamic teachings, namely all aspects that arise in the life of a Muslim whose principles are justice and balance, as well as conformity with the Shari'a, without elements of exaggeration (ifrâṭ) or facilitating a matter (tafrîṭ). Yûsuf al-Qaraḍâwi views manhaj al-wasaṭiyyah as a balance and neutrality between two conflicting sides. One side may not dominate the other side nor eliminate it. One of the sides also does not exceed the level that should be his right so that he wrongs the other side. In his fatwa, al-Qaraḍâwi applies manhaj al-wasaṭiyyah by paying attention to legal balance and compatibility with maqâṣid ash-syarî'at.